A prolonged exposure of human lung carcinoma epithelial cells to benzo[a]pyrene induces p21-dependent epithelial-to-mesenchymal transition (EMT)-like phenotype - Hýžďalová, Martina; Procházková, Jiřina; Strapáčová, Simona; Svržková, Lucie; Vacek, Ondřej; Fedr, Radek; Andrysík, Zdeněk; Hrubá, Eva; Líbalová, Helena; Kléma, Jiří; Topinka, Jan; Mašek, Josef; et al. (Chemosphere, 2021)
Deciphering the role of the aryl hydrocarbon receptor (AhR) in lung cancer cells may help us to better understand the role of toxic AhR ligands in lung carcinogenesis, including cancer progression. We employed human lung carcinoma A549 cells to investigate their fate after continuous two-week exposure to model AhR agonists, genotoxic benzo[a]pyrene (BaP; 1 μM) and non-genotoxic 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD; 10 nM). While TCDD increased proliferative rate of A549 cells, exposure to BaP decreased cell proliferation and induced epithelial-to-mesenchymal transition (EMT)-like phenotype, which was associated with enhanced cell migration, invasion, and altered cell morphology. Although TCDD also suppressed expression of E-cadherin and activated some genes linked to EMT, it did not induce the EMT-like phenotype. The results of transcriptomic analysis, and the opposite effects of BaP and TCDD on cell proliferation, indicated that a delay in cell cycle progression, together with a slight increase of senescence (when coupled with AhR activation), favors the induction of EMT-like phenotype. The shift towards EMT-like phenotype observed after simultaneous treatment with TCDD and mitomycin C (an inhibitor of cell proliferation) confirmed the hypothesis. Since BaP decreased cell proliferative rate via induction of p21 expression, we generated the A549 cell model with reduced p21 expression and exposed it to BaP for two weeks. The p21 knockdown suppressed the BaP-mediated EMT-like phenotype in A549 cells, thus confirming that a delayed cell cycle progression, together with p21-dependent induction of senescence-related chemokine CCL2, may contribute to induction of EMT-like cell phenotype in lung cells exposed to genotoxic AhR ligands.
Keywords: Carcinoma; nádory plic; Lung Neoplasms; Humans; receptory aromatických uhlovodíků; Lung carcinoma; Cell proliferation; Lung; Phenotype; epitelové buňky; lidé; plíce; karcinom; Tumor progression; Epithelial Cells; fenotyp; Receptors, Aryl Hydrocarbon; Benzo(a)pyrene; BaP; EMT; benzopyren; TCDD